Impact of Avian Influenza in Some States of Nigeria - Saidu, L.; Wakawa, A.M.; Abdu, P.A.; Adene, D.F.; Kazeem, H.M.; Ladan, K.C.; Abdu, M.; Miko, R.B.; Fatihu, M.Y.; Adamu, J.; Mamman, P.H. (International Journal of Poultry Science, 2008)
Cases of Avian Influenza (AI) outbreaks reported and confirmed were extracted from the records of control committees on AI in Kano and Katsina States, Veterinary Teaching Hospital of Ahmadu Bello University, Zaria, Pan-African Control of Epizootics (PACE) project office at Kaduna. Information on Al outbreaks in Jigawa State were obtained through a questionnaire. A total of 480,378 birds were lost in 34 outbreaks in the four states under study between the period of January and March 2006. Chickens accounted for more than 99% of all the birds affected followed by guinea fowls and turkeys. More than 60% of the birds affected were adults. The concentrations of poultry farms in Kano metropolis particularly along Gwarzo road where the epidemic was first noticed might have been responsible for the fast spread of the disease within Kano metropolis. It is a common practice to find geese, muscovey ducks and turkeys in one farm in the study area. This practice makes the chickens and turkeys more prone to the disease. From the tract of outbreaks It is possible that the disease spread from Jigawa State to Kano state and from Kano State to other States in the study area and other parts of the country through trade in live birds and poultry by products. For proper diagnosis and control of AI in Nigeria, poultry farmers should be educated on the necessity for prompt disease reporting to veterinarians and appropriate authorities.